Omani Women Participation in Sport and Physical Education Islamic Feminism Review - Alsinani, Yousra Juma (Journal of Educational and Psychological Sciences, 2022)
This paper focuses on reviews of documents and literature relating to Muslim Women’s status generally and in the Omani context specially in sports education. The researcher reviews the literature in two important aspects: first, the Omani Muslim women's identity, its history, as well as the history of physical activities and sports of women in Oman, second the studies about in recent statues of Omani Women in Islam, gender and education.A specific focus will be on Islamic Identity Prospective and reflect that on Feminism and Physical Education in Oman As a result of the study, it can be claimed that the “Islamic Women's Identity” offers alternative approaches in gender relations through which women who choose to adhere to their Islamic identity can exercise their freedom from tradition and rules.
Keywords: Physical Education; Omani women; Islam; Feminism